From sacred landscape to visual commodity: the platformization of cultural space in Indonesian tourism media - Umma Fathimah Sabilah Faradis (CV Narasi Khatulistiwa Indonesia, 2026)
Background: The increasing dependence of tourism promotion on digital platforms has transformed how sacred and culturally significant landscapes are represented, circulated, and consumed within contemporary tourism communication. Objective: This study examines how Indonesian tourism media platformize cultural space and reconfigure sacred landscapes into visually consumable tourism commodities. Method: This study employs a qualitative corpus-based multimodal design using official tourism and heritage communication materials, combining platformization mapping, sacred-to-commodity framing analysis, and multimodal-spatial analysis. Results: Findings indicate that cultural landscapes are systematically organized through platform visibility mechanisms that prioritize discoverability, visual attractiveness, and destination branding. Findings further reveal that sacred and heritage meanings are not removed but selectively rearticulated through experience-oriented narratives emphasizing immersion, accessibility, and tourism engagement. Findings also demonstrate that multimodal resources, including visual framing, spatial composition, symbolic imagery, and textual narratives, construct a tourist gaze that privileges scenic appreciation and destination recognition while maintaining limited references to ritual and cultural significance. Implication: The novelty of this study lies in integrating cultural landscape theory, tourism imaginaries, and platformization perspectives within a unified analytical framework that explains how sacred space is transformed through digital tourism media. Novelty: This study contributes to tourism communication, heritage studies, and multimodal discourse research by advancing a platform-oriented understanding of cultural representation in contemporary tourism environments.